ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KESEJAHTERAAN PENDUDUK DI PROVINSI ACEH - Diana Sapha A.H; Cut Endang K (Universitas Negeri Padang, 2015)
This study aims to identify and analyze the effect of government education expenditure, government health expenditure and government infrastructure expenditure (housing and public facilities) on Human Development Index (HDI) in Aceh Province as an indicator of public welfare. The scope of study is 23 districts/cities in Aceh Province by using secondary data over period 2010-2013. The model used is multiple linear regression using panel data with Random Effect Model. The results show factors that influence on public welfare in Aceh Province are measured by Human Development Index significantly government education expenditure and government health expenditure. While government infrastructure expenditure (housing and public facilities) does not significantly influence the significance level of 5 percent but significant at 10 percent of the Human Development Index (HDI) of Aceh Province. From these results, this study suggests for local government in Aceh to pay attention to the budget set to be better alocated so that the Human Development Index (HDI) or public welfare in Aceh Province will improve. Keyword : public welfare, HDI, government expenditure, panel, REM